[1n]Paracyclophanes - Takemura, Hiroyuki (Current Organic Chemistry, 2009)
[1n]Paracyclophanes ([1n]PCPs) do not often appear in cyclophane chemistry because their synthetic strategies are limited compared to those of general o-, m-, p-[mn]cyclophanes. However, the highly symmetrical and relatively rigid structure of [1n]PCPs has attracted the interest of chemists in the fields of host-guest and molecular recognition chemistry. Some categories of [1n]PCP have been synthesized for application in polymer chemistry, while others were synthesized for synthetic interest or with the aim of investigating their chemical properties. The aims of synthesis are diverse, but the special structures connecting the benzene rings with the various elements are surely attractive from an aesthetic point of view. In this review, the synthetic strategies, structures, and some applications of [1n]PCPs are surveyed.